The role of accounting system in the recovery from the impact of financial crisis (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This study aims to identify the concepts of financial crisis and its reasons of creation , also explain the effects of the accounting disclosure and the International Accounting Standards in current financial crisis, In addition to,  indicate the role of accounting in the reform of the financial system from the impact of financial crisis.             The  methodology of this study orientied to two main aspects, the first is an identifying approach through exploring the opinion of financial experts, the second aspect is based on an analytical approach to satisfy the requirements  of experts to get there opinion on some questions and inquiries written by the researcher, while analyzing the results with some conclusions, the main conclusion is  the shortage of disclosing some material accounting information lead to take some inaccurate decisions by the investors; the second one is the flexibility and the improper use of the accounting standards participated in generating the financial crises, in addition to, the weaknesses of the supervisory organizations on the financial institutions is one of the main reasons behind the current financial crises, The study suggest a number of recommendations relating to the proposed reforms of the financial system to secure a greater role for accounting to not involve into the causes of financial crises.